Preferred Conversation Topics with Respect to Treatment Decisions Among Individuals with Type 2 Diabetes - Tichler A; Hertroijs DFL; Ruwaard D; Brouwers MCGJ; Hiligsmann M; de Jong JD; Elissen AMJ (Patient Preference and Adherence, 2023)
Anna Tichler,1,2 Dorijn FL Hertroijs,1,2 Dirk Ruwaard,1,2 Martijn CGJ Brouwers,2,3 Mickaël Hiligsmann,1,2 Judith D de Jong,1,2,4 Arianne MJ Elissen1,2 1Department of Health Services Research, Faculty of Health, Medicine and Life Sciences (FHML), Maastricht University, Maastricht, the Netherlands; 2Care and Public Health Research Institute (CAPHRI), Maastricht University, Maastricht, the Netherlands; 3Department of Internal Medicine, Division of Endocrinology and Metabolic Disease, Maastricht University Medical Center+, Maastricht, the Netherlands; 4The Netherlands Institute for Health Services Research (NIVEL), Utrecht, the NetherlandsCorrespondence: Anna Tichler, Department of Health Services Research, Faculty of Health, Medicine and Life Sciences (FHML), Maastricht University, P.O. Box 616, Maastricht, 6200 MD, the Netherlands, Tel +31433882193, Email a.tichler@maastrichtuniversity.nlPurpose: Greater knowledge of individuals’ needs and preferences can enhance shared decision-making, which is associated with improved quality of decisions and increased satisfaction. This study aimed to identify and prioritize the attributes (ie conversation topics) that individuals with type 2 diabetes find it most important to discuss with their healthcare provider regarding treatment decisions.Patients and Methods: First, small group interviews were organized with adults with type 2 diabetes (N=8) treated in primary care to identify the attributes that they find important to discuss regarding treatment decisions. A five-step nominal group technique was applied during the interviews. An object best-worst scaling (BWS) survey was subsequently distributed to individuals with self-reported diabetes participating in the Dutch Health Care Consumer Panel of the Netherlands Institute for Health Services Research (N=600) to determine the relative importance score (RIS) of the identified attributes. A higher RIS indicates a higher level of perceived importance. Subgroup and latent class analyses were performed to explore whether individuals’ demographic and disease characteristics influenced their attribute preferences.Results: A total of 21 attributes were identified during three small group interviews with individuals with type 2 diabetes. Respondents in the BWS survey (N=285) viewed “quality of life” (RIS=11.97), “clinical outcomes” (RIS=10.40), “long-term diabetes complications” (RIS=9.83) and “short-term adverse medication” (RIS=7.72) as the most important in the decision-making process for the treatment of type 2 diabetes. Some differences in attribute preferences were identified according to demographic and disease characteristics.Conclusion: In general, individuals with type 2 diabetes not only want to discuss the biological effects of treatments, but also the impact of treatment on their quality of life. Healthcare providers should be aware that attributes are viewed differently by different individuals. This emphasizes the need for tailor-made healthcare decisions, which means eliciting and responding to individual preferences in the decision-making process.Keywords: shared decision-making, person-centered care, patient preferences, diabetes type 2